2020
DOI: 10.3390/jcm10010088
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Therapies in Pheochromocytoma and Paraganglioma: Immune Checkpoint Inhibitors in the Starting Blocks

Abstract: Pheochromocytoma and paraganglioma are neuroendocrine neoplasms, originating in the adrenal medulla and in parasympathetic and sympathetic autonomic nervous system ganglia, respectively. They usually present as localized tumours curable with surgery. However, these tumours may exhibit heterogeneous clinical course, ranging from no/minimal progression to aggressive (progressive/metastatic) behavior. For this setting of patients, current therapies are unsatisfactory. Immune checkpoint inhibitors have shown outst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 44 publications
(52 reference statements)
0
24
0
1
Order By: Relevance
“…These results indicated that the patients with high m6A risk may fail to benefit from ICIs treatment. It is noteworthy that the blockbuster results about the ICIs therapeutic effect on ACC remain unpublished, and several related trials, such as NCT04187404 and NCT02834013, are still ongoing [ 55 ]. Besides, differences in expression thresholds for defining PD-L1 positivity or overexpression make some contradictory results reported [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the patients with high m6A risk may fail to benefit from ICIs treatment. It is noteworthy that the blockbuster results about the ICIs therapeutic effect on ACC remain unpublished, and several related trials, such as NCT04187404 and NCT02834013, are still ongoing [ 55 ]. Besides, differences in expression thresholds for defining PD-L1 positivity or overexpression make some contradictory results reported [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of FDA-approved atezolizumab, avelumab, ipilimumab and pembrolizumab has also been investigated in NENs other than MTC (39,40), thereby confirming a strong interest for ICI therapy in this subset of tumors.…”
Section: Discussionmentioning
confidence: 95%
“…Whereas systemic therapies include radionuclide therapy with 131Imetaiodobenzylguanidine (MIBG) (47) or peptide receptor radionuclide therapy (PRRT) (48), chemotherapy with cyclophosphamide, vincristine and dacarbazine (CVD) (49), or temozolomide (50). Among molecular targeted therapies the effi cacy of TKI as lenvatinib (NCT03008369), cabozantinib (NCT02302833), nivolumab, and ipilimumab (NCT02834013) are currently being evaluated in clinical trials (51). Recently, data from a phase 2 clinical trial provided the rationale for pembrolizumab use in patients with advanced PGLs (52).…”
Section: Discussionmentioning
confidence: 99%